Influence of Irrigation, Crop Residue Mulch and Nitrogen Management Practices on Soil Physical Quality - S. Pradhan, R. Singh; S.P. Datta, Sumanta Chatterjee, K.K. Bandyopadhyay (Journal of the Indian Society of Soil Science, 2017)
Improvement in soil structure is a prerequisite for maintaining soil physical health/quality and for sustaining agricultural productivity at higher level. Field experiments were conducted during the kharif season of 2012 and 2013 on maize crop in a sandy loam soil to study the impact of different management practices viz., irrigation, crop residue mulch and nitrogen (N) fertilization on soil physical quality indices like least limiting water range (LLWR), S index, mean weight diameter (MWD), water stable aggregates (%WSA) and whole soil stability index (WSSI), and their impact on crop growth and yield. Maize (cv HQPM 1) was grown in a split-split plot design with two levels of irrigation (irrigated and rainfed), two levels of mulch (no mulch and wheat residue mulch @ 10 t ha-1) and three levels of N (0, 75 and 150 kg N ha-1). Soil physical quality parameters such as S index, LLWR, MWD, %WSA and WSSI increased due to irrigation, crop residue mulching and N application. Application of irrigation, mulch and N @ 150 kg ha-1 significantly increased the S index by 3.5, 9.9 and 4.3 per cent, respectively compared to the respective control treatments (rainfed, no mulch and no N treatments). Crop residue mulching significantly increased LLWR by 48.3, 11.4 and 31.6 per cent over no-mulch treatment at 0-15 cm soil depth at 67 days after sowing (DAS), 95 DAS and harvest, respectively. Application of irrigation registered significantly higher MWD by 21.4 per cent after maize harvest over the rainfed treatment, whereas, mulching increased MWD by 6.7 per cent after maize harvest than no-mulch treatment. After maize harvest, mulching registered significantly higher WSA by 7.8 per cent over the no-mulch treatment. The root growth, grain and biomass yield of maize was significantly correlated with the saturated hydraulic conductivity of soil at 0-15 cm soil depth. Therefore, growing maize crop with need based irrigation at critical growth stages, N application @ 150 kg ha-1 and crop residue mulching @ 10 t ha-1 resulted in better soil physical quality and maize yield in sandy loam soil of Delhi region.